Comparative analysis offemale charactersin the novelsCaoXuechin «Dream of the Red Chamber » and M. Auezov «Abai’s Way» (Journal of Oriental Studies, 2016)
This article discusses acomparative analysis offemale charactersin the novelsCaoXuechin «Dream of the Red Chamber» and M.Auezov»Abai’s Way». Comparetiveanalyzethe components ofthe unit-Onimtaken fromthework ofCaoXuechin»Dream of the Red Chamber» and M.Auezov»Abai’s Way».These fragmentsstudies showthe specificity ofimagesof female characters in Chinese and Kazakh literaturethat reflect theparticularworldviewof storage medialanguages.
Keywords: portrait; national character; onomastics; ethno-culturalinformation; language factor; the psychologicalaspect.